2022
DOI: 10.1101/2022.01.02.22268629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive predictors of vaccine hesitancy and COVID-19 mitigation behaviors in a population representative sample

Abstract: With the continued threat of COVID-19, predictors of vaccination hesitancy and mitigation behaviors are critical to identify. Prior studies have found that cognitive factors are associated with some COVID-19 mitigation behaviors, but few studies employ representative samples and to our knowledge no prior studies have examined cognitive predictors of vaccine hesitancy. The purpose of the present study, conducted among a large national sample of Canadian adults, was to examine associations between cognitive vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Most studies used samples of adults ( N = 26). Sixteen studies addressed vaccine hesitancy (i. e., doubts concerning the reception of a COVID‐19 vaccine) 6 , 7 , 8 , 16 , 17 , 29 , 33 , 34 , 37 , 39 , 44 , 45 , 46 , 47 , 48 , 50 and 14 studies explored vaccine unwillingness (i.e., the likelihood of refusing a COVID‐19 vaccine). 28 , 30 , 32 , 35 , 36 , 38 , 40 , 41 , 42 , 43 , 46 , 49 , 51 , 52 The characteristics of the studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies used samples of adults ( N = 26). Sixteen studies addressed vaccine hesitancy (i. e., doubts concerning the reception of a COVID‐19 vaccine) 6 , 7 , 8 , 16 , 17 , 29 , 33 , 34 , 37 , 39 , 44 , 45 , 46 , 47 , 48 , 50 and 14 studies explored vaccine unwillingness (i.e., the likelihood of refusing a COVID‐19 vaccine). 28 , 30 , 32 , 35 , 36 , 38 , 40 , 41 , 42 , 43 , 46 , 49 , 51 , 52 The characteristics of the studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Vaccine hesitancy was reported to be related to several factors including concerns that receiving a vaccine has more risks than benefits, 6 , 29 fear of side effects, 6 , 39 , 47 belief that insufficient research had been conducted on the vaccine, 29 , 47 , 48 mistrust in vaccines, 8 , 39 , 44 insufficient time to reflect on accepting the vaccine, 8 having an incomplete vaccination history, 16 , 29 , 33 believing that COVID‐19 will not affect the person or the people around them, 6 , 16 , 29 , 44 living in rural areas, 50 holding more conservative political views, 6 and poorer executive functions. 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proactive coping and anxiety about contracting COVID-19 reflect future-oriented behaviors and cognitions, which may have a role in the adoption of health-related behavior. Recent research showed that people with a future-oriented thinking style were more likely to take the COVID-19 vaccine and engage in precautionary health-related behaviors, such as social distancing and wearing a mask [5]. Proactive coping represents effortful steps to modify or avoid a stressor before it occurs [6].…”
mentioning
confidence: 99%
“…Despite efforts to address vaccine skepticism and mistrust by increasing public health messaging focused on vaccine safety, COVID‐19 vaccination rates remain suboptimal in the United States [4]. Repeating scientific evidence to debunk vaccine misinformation and demonstrate vaccine safety and effectiveness may not be enough to change anti‐vaccination attitudes and beliefs [5]. Identifying predictors of vaccine hesitancy may provide alternative avenues for tailoring public health messaging to increase vaccination uptake and encourage people to continue to stay up to date on their vaccines.…”
mentioning
confidence: 99%